Quantum transport through Ga2As2 cluster. Issue 3 (10th June 2014) - Liu, Fu-Ti; Cheng, Yan; Yang, Fu-Bin; Chen, Xiang-Rong
Abstract : The electronic transport properties of Ga2 As2 cluster, which is sandwiched between two semiinfinite Au (1 0 0)-3 × 3 pyramical-shaped electrodes with the Ga-Ga axis of the cluster parallel to the transport direction and the As-As axis of the cluster parallel to the transport direction, respectively, is investigated with a combination of density functional theory and the non-equilibrium Green's function method. We have simulated the nanoscale junctions breaking process and found that the conductance of cluster decreases then increases when the contact is pulled apart in two configurations. We analyzed the difference of conductance from transmission spectra and projected density of states, and calculated the I-V characteristics of devices in this two configurations when d z = 2.0 Å. The I-V curves display a linear characteristics in the voltage range of 0 ∼ 2.2 V. The negative differential resistance appears within a small range of voltage in the junctions with As-As axis of the cluster parallel to the transport direction when bias is larger than 2.2 V.